Effectiveness of Sargassum sp. ethanolic extract on traumatic ulcers healing in the labial mucosa of Wistar strain (Rattus norvegicus) - Arwidasari, Annisya Ristie; Cevanti, Twi Agnita; Soewondo, Isidora Karsini (Padjadjaran Journal of Dentistry, 2019)
Introduction: Oral ulcer lesions are one of the most common lesions in the oral cavity. The prevalence of traumatic ulcers is quite high compared to other oral lesions. Brown algae, Sargassum sp. is one of the algae contains flavonoids, vitamin A, vitamin C, iron, and calcium, which play a role in wound healing and has economic value. This study was aimed to determine the effectiveness of Sargassum sp. ethanolic extract on traumatic ulcers healing in the labial mucosa of Wistar strain (Rattus norvegicus). Methods: 28 Wistar strain (Rattus norvegicus) weighed 150-200 grams. The samples were divided into 4 groups (K1, K2, P1, P2); each group consisted of 7 mice. K1 group was administered with Hydroxy Propyl Methyl Cellulose (HPMC), K2 was administered with 0.2% hyaluronic acid gel, P1 was administered with 50% Sargassum sp. extract gel, and P2 was administered with 75% Sargassum sp. extract gel. In each group, the ulcer was made on the mice labial mucosa; then the ulcer diameter was measured and observed on day 1 and day 7. Results: The mean diameter ± standard deviation of traumatic ulcer calculations were K1 (1.09 ± 0.40), K2 (1.81 ± 0.67), P1 (1.39 ± 0.43) and P2 (2.16 ± 0.49) respectively. One way ANOVA test results showed significant differences in K1, K2, P1, and P2 groups. Conclusion: Ethanol extract of Sargassum sp. is effective in accelerating the traumatic ulcers healing at the concentration of 75%.Keywords: Traumatic ulcer, Sargassum sp., wound healing.